Analysis of Marketing Mix (4P) Influence on Automotive Purchase Decisions at PT. XYZ - Elsa Alvina Kambuayo; Andry Herawati; Damajanti Sri Lestari; Dian Ferriswara (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study investigates the influence of the marketing mix (product, price, promotion, and place) on purchase decisions for automotive products at PT. XYZ Sidoarjo. Using a quantitative approach, data were collected from 150 consumers who had purchased vehicles, spare parts, or services within the last six months. A structured questionnaire measured the four marketing mix elements and purchase decision using a 5-point Likert scale. Multiple linear regression analysis was applied to test the partial and simultaneous effects of the independent variables on the dependent variable. The results indicate that all four elements significantly and positively affect purchase decisions, with price emerging as the most dominant factor. The model’s Adjusted R² value of 0.915 shows that the marketing mix variables explain 91.5% of the variation in purchase decisions. These findings reinforce the relevance of the 4P framework in the automotive sector and highlight the need for integrated marketing strategies. Practically, the study suggests that PT. XYZ Sidoarjo should focus on maintaining competitive pricing, enhancing product quality and innovation, optimizing promotional activities—especially digital marketing—and strengthening distribution channels to sustain competitiveness in a dynamic market. In addition to these findings, the study provides insight into consumer behavior within the automotive industry, particularly in a highly competitive market like Sidoarjo. Consumers are increasingly sensitive to pricing structures, especially given the economic pressures and the availability of alternative brands. Price sensitivity, therefore, should be a focal point in shaping future marketing strategies. Companies need to conduct regular market analysis to ensure their pricing aligns with customer expectations and perceived value.